1998
DOI: 10.1098/rspb.1998.0319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of articulate brachiopod nuclear and mitochondrial gene trees leads to a clade–based redefinition of protostomes (Protostomozoa) and deuterostomes (Deuterostomozoa)

Abstract: Nuclear and mtDNA sequences from selected short-looped terebratuloid (terebratulacean) articulate brachiopods yield congruent and genetically independent phylogenetic reconstructions by parsimony, neighbour-joining and maximum likelihood methods, suggesting that both sources of data are reliable guides to brachiopod species phylogeny. The present-day genealogical relationships and geographical distributions of the tested terebratuloid brachiopods are consistent with a tethyan dispersal and subsequent radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…16S rates are ~1.4 times 12S rates). Thus, both comparisons indicate that the brachiopod sequences described here may evolve slowly, in keeping with the unusually deep phylogenetic resolution obtained from brachiopod 12S sequences (Cohen et al 1998c). …”
Section: Rate Of Molecular Evolution and Phylogeography Of Atlantic Amentioning
confidence: 76%
See 3 more Smart Citations
“…16S rates are ~1.4 times 12S rates). Thus, both comparisons indicate that the brachiopod sequences described here may evolve slowly, in keeping with the unusually deep phylogenetic resolution obtained from brachiopod 12S sequences (Cohen et al 1998c). …”
Section: Rate Of Molecular Evolution and Phylogeography Of Atlantic Amentioning
confidence: 76%
“…In other previous work, analyses of an alignment of 12S rDNAs from a wide taxonomic range of shortlooped brachiopods including cancellothyridids gave evidence of strong phylogenetic signal and stationary base composition (Cohen et al 1998c). In the new 12S alignment described here, phylogenetic signal was high (g1 from 10,000 random trees and 80 informative characters = -0.86, P < 0.01, Hillis and Huelsenbeck 1992) and base composition again showed no heterogeneity (P = 1.00, 84 d. f.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are other signi¢cant di¡er-ences between phoronids, brachiopods and the spiralian protostome phyla based on the structure of the larval serotonergic nervous system. The type 5 system de¢nes a pattern which obviously groups the phoronids and brachiopods with the deuterostomes and is thus just one more character where anatomical data di¡er from 18S rDNA sequence data (Nielsen 1995;Cohen et al 1998). Recently, Zrzavy et al (1998) concluded that the a¤lia-tion of the brachiopods and phoronids to the spiralian phyla based on rDNA sequences is an out-group artefact and may not re£ect a real relationship.…”
Section: (B) Con£ict Between 18s Rdna and Anatomical Data?mentioning
confidence: 99%